INTEGRATING TECHNOLOGY INTO ENGLISH LANGUAGE TEACHING: OPPORTUNITIES AND CHALLENGES (Modern education and development, 2025)
The integration of technology into English language teaching (ELT) has revolutionized traditional pedagogical practices. This paper explores the benefits and limitations of using digital tools in English as a Foreign Language (EFL) classrooms. Through an analysis of modern platforms, multimedia resources, and virtual communication tools, the study examines how technology can enhance language acquisition, learner engagement, and teaching efficiency. Simultaneously, it addresses challenges such as digital literacy, infrastructure gaps, and pedagogical adjustments. The findings suggest that while technology opens new dimensions in ELT, its successful implementation depends on strategic planning, teacher readiness, and institutional support.